Markers infectious agent in the cord blood samples public register of donors - A. B. Smoljaninov; D. A. Ivolgin; I. I. Maslennikova; O. V. Supil’nikova; I. A. Pirozhkov; A. D. Krjuchkova (Журнал инфектологии)
Objective. To evaluate the distribution of markers of infectious agents in umbilical cord blood samples Pokrovskij public stem cell bank donor registry for five years (2009 – 2013).Materials and Methods. 3533 plasma samples were investigatedafter selection during cord blood processing procedure for allogeneic use in Pokrovskij stem cell bank. All plasma samples were investigated in accordance with the Order of the Ministry of Health № 325 – 2003 by enzymelinked immunoassay method. In addition, during the period from November 2011 to December 2013 1030 plasma samples of umbilical cord blood were examined for the presence of HCV RNA, the RNA of HIV and HBV DNA.Results. Markers of the agents above have not been found in the plasma of 481 samples (13.6%). During the described period, no significant change in the share of samples containing antibodies to cytomegalovirus and toxoplasmosis (cytomegalovirus – 1978 samples (56%), Toxoplasma gondii – 112 samples (3.2%), 825 samples (23.4%) cytomegalovirus and Toxoplasma gondii simultaneously) were registered. 137 samples (3.9%) were subjected to utilization in connection with detection of antibodies to HbcorAg – 116 samples (3.3%), antibodies to HCV – five samples (0.14%), and antibodies to Treponema pallidum – 16 samples (0.45%).Conclusion. The introduction of an additional method of polymerase chain reaction for the detection of nucleic acids of hepatitis viruses B, C, human immunodeficiency virus, along with study of cord blood samples by enzyme-linked immunoassay improve the quality of the control of the transmission of blood-borne infections.